Psychological distress among AIDS orphans in rural Uganda - Atwine, Benjamin; Cantor-Graae, Elizabeth; Bajunirwe, Francis (Social Science & Medicine, 2005)
More than 11 million children under 15 years in sub-Saharan Africa have lost at least one parent to AIDS. In Uganda, about 2 million children are orphans, with one or both parents dead. The objective of this study was to investigate the psychosocial consequences of AIDS orphanhood in a rural district in Uganda and to identify potential areas for future interventions. The study was conducted in a randomly selected sub-county in Bushenyi District in Uganda. The study population consisted of 123 children aged 11–15 years whose parents (one or both) were reported to have died from AIDS and 110 children of similar age and gender living in intact households in the same neighbourhood. Symptoms of psychological distress were assessed using the Beck Youth Inventories of Emotional and Social Impairment (BYI). The standardized interview also included questions concerning current and past living conditions. A multivariate analysis of factors with possible relevance for BYI outcome showed that orphan status was the only significant outcome predictor. Orphans had greater risk (vs. non-orphans) for higher levels of anxiety (odds ratios (OR) ¼ 6.4), depression (OR ¼ 6.6), and anger (OR ¼ 5.1). Furthermore, orphans had significantly higher scores than non-orphans on individual items in the Beck Youth Depression Inventory that are regarded as particularly ‘‘sensitive’’ to the possible presence of a depressive disorder, i.e. vegetative symptoms, feelings of hopelessness, and suicidal ideation. High levels of psychological distress found in AIDS orphans suggest that material support alone is not sufficient for these children.
Keywords: HIV; AIDS; Orphans; Psychological distress; Uganda; Rural health